ANALYSIS OF TARGETED RESEARCH IN 20-30 YEARS OF THE XX CENTURY - Bobir Axmadjon ogli Odilov, Nodir Rakhmonqulovich Karimov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the 1920s and 1930s, the study of the economic nature of the peoples of Uzbekistan and Central Asia in general became of scientific and practical importance and began to serve the introduction of reforms in the agrarian and economic activities of the Soviet government. The research has been widely used to involve ethnographers in various fields, as well as experts in various fields, to change social property relations in public life and to promote the policy of collectivization in agriculture. The researchers stressed the need to study the long-established traditions of the Uzbek people in the field of hashar, collective farming, which covered all the densely populated areas of Uzbekistan. It should be noted that the traditional forms of economy (especially "paykal"), which are based on private property relations, were in fact interpreted in accordance with the formation of common (public, state) property. In this paper, studies that reflect the traditions of collective farming on the ground are systematized and compared.